2019
DOI: 10.21608/pssjn.2020.21020.1010
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of applying fatigue Nursing Guidelines on Oncology Patient Health Outcome

Abstract: Background: Cancer related fatigue recognizes as one of the most regularly stated and distressing side effects reported by most of cancer patients and significant has long-term effect on the quality of life. Indeed, Fatigue can affect on the patient's life including physical, psychological, social and spiritual aspects. Aim: evaluate the effect of applying fatigue nursing guidelines on oncology patient health outcome. Research design: Quasi experimental design was used in this study. Sample: A convenient sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…The results also matched with the study done by, Elshahat et al (32) who applied fatigue nursing guidelines on oncology patient and reported that, the fatigue severity at baseline assessment was sever by mean of ±SD 7.77±1.45 then it decreased at onemonth after fatigue nursing care guidelines to 4.76±1.95 to be moderate while. it raised slightly again after the three-month of the nursing care guidelines implementation but still moderate level fatigue with means of 6.03±1.73.…”
Section: (30)supporting
confidence: 89%
“…The results also matched with the study done by, Elshahat et al (32) who applied fatigue nursing guidelines on oncology patient and reported that, the fatigue severity at baseline assessment was sever by mean of ±SD 7.77±1.45 then it decreased at onemonth after fatigue nursing care guidelines to 4.76±1.95 to be moderate while. it raised slightly again after the three-month of the nursing care guidelines implementation but still moderate level fatigue with means of 6.03±1.73.…”
Section: (30)supporting
confidence: 89%